A global analysis of deforestation due to biofuel development - Gao, Y.; Skutsch, M.; Masera, O.; Pacheco, P. (Center for International Forestry Research, 2011)
This report examines whether the recent increase in biofuel feedstock production is resulting in increased deforestation rates and magnitudes within tropical regions. It reviews several methodological challenges for undertaking this analysis, and presents a set of preliminary findings. The analysis is focused on three regions from a global perspective: Latin America, southeast Asia, and sub-Saharan Africa. The report deals only with agriculture-based feedstocks such as sugarcane, soya, palm oil and jatropha, known also as first generation biofuels, because second generation biofuels from wood or other lignocelullosic materials have not yet been produced on a commercial scale. The analysis centres on the years since 2000 due to the marked increase in biofuel production since then.